$$ \mbox{How would I prove}\quad \int_{0}^{\infty} {\ln\left(\,\tan^{2}\left(\, ax\,\right)\,\right) \over 1 + x^{2}}\,{\rm d}x =\pi \ln\left(\,\tanh\left(\,\left\vert\, a\,\right\vert\,\right)\,\right)\,{\Large ?}. \qquad a \in {\mathbb R}\verb*\* \left\{\,0\,\right\} $$

  • $\begingroup$ Doesn't look like the indefinite integral has a elementary closed form. $\endgroup$
    – Joe
    Jan 27 '13 at 3:27
  • 1
    $\begingroup$ See here: math.stackexchange.com/questions/285960/… (essentially the same thing, asked a few days ago) $\endgroup$
    – L. F.
    Jan 27 '13 at 3:49
  • $\begingroup$ $\ln y^2=2\ln y$ $\endgroup$
    – Lucian
    Nov 17 '13 at 23:26
  • $\begingroup$ @Ethan It should be $\displaystyle\large \pi\ln\left(\,\tanh\left(\,\left\vert\, a\,\right\vert\,\right)\,\right)\,,\quad a \not= 0$. $\endgroup$ Nov 17 '14 at 5:02

Here is another solution:

We remark that

$$ \log\tan^{2}\theta = -4 \sum_{n \ \mathrm{odd}}^{\infty}\frac{1}{n}\cos 2n\theta \tag{1} $$


$$ \sum_{n \ \mathrm{odd}}^{\infty} \frac{1}{n} x^{n} = \frac{1}{2}\log\left(\frac{1+x}{1-x}\right). \tag{2} $$

Both are easily proved by using Euler's formula $e^{i\theta} = \cos\theta + i\sin\theta$ and the Taylor series of the logarithm. Also we note that

$$ \int_{0}^{\infty} \frac{t \sin t}{a^2 + t^2} \, dt = \frac{\pi}{2} e^{-|a|}. \tag{3}$$


\begin{align*} \int_{0}^{\infty} \frac{\log\tan^2(ax)}{1+x^2} \, dx &= \int_{0}^{\infty} \log\tan^2(ax) \left( \int_{0}^{\infty} \sin t \, e^{-xt} \, dt \right) \, dx \\ &= \int_{0}^{\infty} \sin t \int_{0}^{\infty} e^{-tx} \log\tan^2(ax) \, dxdt \\ &= -4 \int_{0}^{\infty} \sin t \int_{0}^{\infty} \sum_{n \ \mathrm{odd}}^{\infty}\frac{1}{n} e^{-tx} \cos (2nax) \, dxdt \\ &= -4 \int_{0}^{\infty} \sin t \sum_{n \ \mathrm{odd}}^{\infty}\frac{1}{n} \frac{t}{4a^{2}n^{2} + t^{2}} \, dt \\ &= -4 \sum_{n \ \mathrm{odd}}^{\infty} \frac{1}{n} \int_{0}^{\infty} \frac{t \sin t}{4a^{2}n^{2} + t^{2}} \, dt \\ &= -2\pi \sum_{n \ \mathrm{odd}}^{\infty} \frac{1}{n} e^{-2an} = \pi \log \left( \frac{1-e^{-2a}}{1+e^{-2a}} \right) \\ &= \pi \log (\tanh a). \end{align*}

  • 1
    $\begingroup$ Very nice. Where did you learn these techniques? I have seen you give similar impressive integral computations on many other questions. $\endgroup$
    – Potato
    Jan 27 '13 at 4:02
  • 2
    $\begingroup$ @Potato, Actually I learned these techniques by myself. But I think that many other people are already aware of these. $\endgroup$ Jan 27 '13 at 4:19
  • $\begingroup$ How did you learn them? Was there a book or paper that was especially useful? I've seen similar tricks ("backwards" conversion of terms to integrals, power series) used by a few physicists, so I wonder if these techniques are taught in books on mathematical methods for physics. $\endgroup$
    – Potato
    Jan 27 '13 at 4:24
  • $\begingroup$ @sos440: this proof is good for a collection with very nice proofs (+1) :-) $\endgroup$ Jan 27 '13 at 9:20
  • $\begingroup$ +1 Very nice! Though I think there's still some need to say a word of two about the interchange of integral and sum from the 3rd to the 4th line...I really loved this one. $\endgroup$
    – DonAntonio
    Jan 27 '13 at 9:47

An idea with complex contour. Let us choose the path

$$C_R:=[-R,R]\cup\gamma_R:=\{z\in\Bbb C\;;\;z=Re^{it}\,\,,\,0\leq t\leq \pi\}\,\,,\,0<<R\in\Bbb R$$

Take the function

$$f(z):=\frac{\operatorname{Log}(\tan^2az)}{1+z^2}=2\frac{\operatorname{Log}(\tan az)}{1+z^2}$$

Inside the domain enclosed by $\,C_R\,$ above, the function has the pole $\,z=i\,$ (note that at the poles of $\,\tan az\,$ the logarithmic function equals $\,0+\arg(\text{pole})\,$ , and since we're going to choose the branch along the cut from zero to $\,-i\infty \,$ , i.e. the negative y-axis all these give us zero, so we're left only with the zero of the denominator in the positive half complex plane:

$$Res_{z=i}(f)=2\lim_{z\to i}(z-i)\frac{\operatorname{Log}(\tan az)}{z^2+1}=2\frac{\operatorname{Log}(\tan ai)}{2i}=-i\log(\tanh a)$$

We also have that

$$\left|\int_{\gamma_R}2\frac{\operatorname{Log}(\tan az)}{1+z^2}dz\right|\leq2\frac{|\log|\tan az||}{1-R^2}R\pi\xrightarrow[R\to\infty]{}0$$

as using the form (with $\,z=x+yi\,\,,\,x,y\in\Bbb R\,\,,\,y>0\,$)

$$\tan az=\frac{e^{2aiz}-1}{e^{2aiz}+1}\Longrightarrow |\log|\tan az||\leq \left|\log\frac{1+e^{2iy}}{1-e^{2iy}}\right|\xrightarrow [y\to\infty]{}\log 1=0$$

Thus, we finally get by Cauchy's Theorem

$$2\pi i(-i\log(\tanh a))=2\pi\log(\tanh a)=\oint_{C_R} f(z)\,dz=$$

$$=\int\limits_{-R}^R\frac{\log(\tan^2 ax)}{1+x^2}dx+\int_{\gamma_R}f(z)\,dz\xrightarrow[R\to\infty]{}\int\limits_{-\infty}^\infty\frac{\log(\tan^2 x)}{1+x^2}dx$$

Now just divide by two the integral of the even function above and we're done.

  • $\begingroup$ "Infinitely many branch...*points*...? Along the real axis? No and no to both your questions. Read here in "branch cuts" and around: en.wikipedia.org/wiki/Complex_logarithm#Branch_cuts $\endgroup$
    – DonAntonio
    Mar 13 '13 at 23:16
  • $\begingroup$ @RandomVariable, I think you don't quite know exactly what a branch cut is (not point). Google it, read it books, in the link I sent you...At the origin, $\log z\,$ isn't defined... but...that's not the matter: if you go "around" $\,z=0\,$ , the argument of complex numbers increases (or decreases, depending on the spinning direction) by an integer multiple of $\,2\pi\,$, and this makes the value of $\,\log z:= \log|z|+i\arg z\,$ multivalued, and from here that branch cutes are chosen to "prevent" that spinning and make $\,\log\,$ single valued...it's too messy to explain here. $\endgroup$
    – DonAntonio
    Mar 14 '13 at 2:10

Denote the evaluated integral as $I$, then $I$ may be rewritten as $$I=\int_0^\infty \frac{\ln \sin^2 ax}{1+x^2}\,dx-\int_0^\infty \frac{\ln \cos^2 ax}{1+x^2}\,dx$$ Using Fourier series representations of $\ln \sin^2 \theta$ and $\ln \cos^2 \theta$, $$\ln \sin^2 \theta=-2\ln2-2\sum_{k=1}^\infty \frac{\cos2k\theta}{k}$$ and $$\ln \cos^2 \theta=-2\ln2+2\sum_{k=1}^\infty (-1)^{k+1}\frac{\cos2k\theta}{k}$$ also note that $$\int_0^\infty\frac{\cos bx}{1+x^2}\,dx=\frac{\pi e^{-b}}{2}$$ then $$\begin{align}I&=-2\sum_{k=1}^\infty \frac{1}{k}\int_0^\infty\frac{\cos2kax}{1+x^2}\,dx-2\sum_{k=1}^\infty \frac{(-1)^{k+1}}{k}\int_0^\infty\frac{\cos2kax}{1+x^2}\,dx\\&=-\pi\sum_{k=1}^\infty \frac{e^{-2ak}}{k}-\pi\sum_{k=1}^\infty (-1)^{k+1}\frac{e^{-2ak}}{k}\\&=\pi\ln\left(1-e^{-2a}\right)-\pi\ln\left(1+e^{-2a}\right)\\&=\pi\ln\left(\frac{1-e^{-2a}}{1+e^{-2a}}\right)\\&=\pi\ln\left(\tanh a\right)\end{align}$$


By equating the real parts on both sides of the identity $$\sum_{k=1}^{\infty} \frac{(be^{i \theta })^{k}}{k} = -\log(1-be^{i \theta}) \ , \ |b| < 1,$$ one finds that $$ \sum_{k=1}^{\infty} \frac{b^{k} \cos k\theta }{k} = - \frac{1}{2} \log \left(1-2b \cos \theta +b^{2} \right).$$

Then for $a >0$, $$ \begin{align}\int_{0}^{\infty} \frac{\log(1-2b \cos 2ax +b^{2})}{1+x^{2}} \ dx &= -2\int_{0}^{\infty}\frac{1}{1+x^{2}}\sum_{k=1}^{\infty} \frac{b^{k} \cos (2akx)}{k} \\ &=-2 \sum_{k=1}^{\infty} \frac{b^{k}}{k}\int_{0}^{\infty} \frac{\cos (2ak x)}{1+x^{2}} \ dx \\ &=-\pi \sum_{k=1}^{\infty} \frac{(be^{-2a})^{k}}{k} \\ &= \pi \log(1-be^{-2a}). \end{align}$$

Letting $b \to 1^{-}$, $$ \int_{0}^{\infty} \frac{\log (4 \sin^{2} ax)}{1+x^{2}} \ dx = \pi \log(1-e^{-2a}). \tag{1}$$

While letting $b \to -1^{+}$, $$\int_{0}^{\infty} \frac{\log(4 \cos^{2} ax)}{1+x^{2}} \ dx = \pi\log(1+e^{-2a}). \tag{2}$$

Then subtracting $(2)$ from $(1)$, $$ \int_{0}^{\infty} \frac{\log (\tan^{2} ax)}{1+x^{2}} \ dx = \pi \log \left(\frac{1-e^{-2a}}{1+e^{-2a}} \right) =\pi \log( \tanh a) .$$


Another approach. We may assume $a>0$, then: $$ I = \int_{0}^{+\infty}\frac{\log\tan^2(ax)}{1+x^2}\,dx = a\int_{0}^{+\infty}\frac{\log\tan^2(x)}{a^2+x^2}\,dx \tag{1}$$ and since $\log\tan^2(x)$ is a $\pi$-periodic function, $$\begin{eqnarray*} I &=& a \int_{0}^{\pi}\log\tan^2(x)\sum_{k\geq 0}\frac{1}{a^2+(x+k\pi)^2}\,dx\\&=&a\int_{0}^{\pi/2}\log\tan^2(x)\sum_{k\geq 0}\left(\frac{1}{a^2+(x+k\pi)^2}+\frac{1}{a^2+(\pi-x+k\pi)^2}\right)\,dx\\&=&2a\int_{0}^{\pi/2}\log\tan(x)\,\frac{\coth(a-ix)+\coth(a+ix)}{2a}\,dx\tag{2} \end{eqnarray*}$$ where the last identity comes from considering the logarithmic derivative of the Weierstrass product for the $\sinh$ function. Now the substitution $x=\arctan t$ brings that integral into:

$$\begin{eqnarray*} && 2\int_{0}^{+\infty}\frac{\log(t)}{1+t^2}\cdot\frac{\sinh(a)\cosh(a)+t^2\sinh(a)\cosh(a)}{\sinh(a)^2+t^2\cosh(a)^2}\,dt\\&=&\int_{0}^{+\infty}\frac{2\sinh(a)\cosh(a)\log(t)\,dt}{\sinh(a)^2+t^2\cosh^2(a)} \tag{3}\end{eqnarray*}$$ that is an elementary integral, just depending on:

$$ \int_{0}^{+\infty}\frac{\log(t)}{1+A^2 t^2}\,dt = \color{red}{-\frac{\pi\log(A)}{2A}}\tag{4} $$

that holds by a symmetry argument.

This is just a small variation on a one-line proof of $\int_{-\infty}^{+\infty}\frac{\sin x}{x}\,dx=\pi$:

$$ \begin{eqnarray*}\int_{-\infty}^{+\infty}\frac{\sin x}{x}\,dx = \int_{-\pi/2}^{\pi/2}\sin(z)\sum_{m\in\mathbb{Z}}\frac{(-1)^m}{z+\pi m}\,dz=\int_{-\pi/2}^{\pi/2}\sin(z)\csc(z)\,dz = \color{red}{\pi}.\end{eqnarray*}$$


Another approach: $$ I(a) = \int_{0}^{+\infty}\frac{\log\tan^2(ax)}{1+x^2}\,dx$$

first use "lebniz integral differentiation" and then do change of variable to calculate the integral.

Hope it helps.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.